Spiritual Health as a Predictor of Social and General Health in University Students? A Study in Iran - Farshadnia, Elahe (Pastoral psychology, 2018)
Spiritual health is considered a major asset that is associated with an individual's perception of their health status. Social health and general health are also two important dimensions of health through which we measure our individual and social performance in the life. The measurement of spiritual and social health in past studies has been done by non-native questionnaires (it means they weren't developed by Iranian researchers), even though these dimensions are highly dependent on Iranian culture. The purpose of this study was to investigate the ability of spiritual health to predict the general and social health of students from Iran University of Medical Sciences in the 2017-18 academic year, using two native questionnaires plus an existing questionnaire. The statistical population of this cross-sectional method consisted of students from Iran University of Medical Sciences. For this purpose, 233 students were selected using a stratified random sampling method. To collect the data, questionnaires on spiritual health, social health, and general health were employed. Data were analyzed using the Pearson correlation and regression methods. Findings indicated a significant relationship between spiritual health and social health (P < 0.01), spiritual health and general health (p < 0.05), and social health and general health (P < 0.01). In addition, spiritual health was a significant predictor of social health and general health, although the prediction power was low. Investigating the role of health dimensions in students using native questionnaires is an important subject. Spiritual health appears to be associated with general, mental, and social health. This relationship also allows the prediction of other dimensions of health in students based on spiritual health.